2020
DOI: 10.3390/healthcare8030317
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Healthy Ageing, Healthy Status and Community Nursing Needs among the Rural Elderly in an Empty Nest Family: Results from the China Health and Retirement Longitudinal Study

Abstract: Health care for the rural elderly in and empty nest family is a major problem in such an ageing society such as China. Based on previous studies, China’s rural health care services only focus on the physical health of the elderly, while public health care services only provide primary services such as blood pressure and blood glucose measurement. This leads to the question of whether physical health is the most important issue for the Chinese rural empty nest elderly (CREE). It is necessary to find out their h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…As age increases, empty nesters' health capital depletion begins to accelerate, and their ability and energy to participate in social activities gradually decreases. Instead of being positively in uenced, participation in social activities among elderly empty nesters may be counterproductive and induce the emergence of various hidden symptom problems [26][27]. The results of chronic disease variables show that having a chronic disease leads to poorer physical health, mental health, and self-rated health among empty nesters [28].…”
Section: Heterogeneity Testmentioning
confidence: 99%
“…As age increases, empty nesters' health capital depletion begins to accelerate, and their ability and energy to participate in social activities gradually decreases. Instead of being positively in uenced, participation in social activities among elderly empty nesters may be counterproductive and induce the emergence of various hidden symptom problems [26][27]. The results of chronic disease variables show that having a chronic disease leads to poorer physical health, mental health, and self-rated health among empty nesters [28].…”
Section: Heterogeneity Testmentioning
confidence: 99%
“…When the health system neglects the older adults, they feel threatened and distrust the health system. 47 Another finding of this study was the absence of a significant relationship based on trust between older adults and nurses. This concept covered limited and inappropriate relationships, lack of participation, and the older adults' dissatisfaction with the care program.…”
Section: Discussionmentioning
confidence: 67%
“…This may be explained by parental sacrifice , that is, parents tend to give up their personal needs for the sake of developmental needs of their children [ 69 ]. This study also found that many rural empty-nest elderly would not like to trouble their children and thus hide the bad news about their health from their children, which is another example of parental sacrifice in China [ 70 , 71 ]. In addition to health problems, most aging parents would prefer not to bother their adult children with their other personal problems.…”
Section: Discussionmentioning
confidence: 98%